Minimal water activity for enterotoxin A production and growth of Staphylococcus aureus. - Lotter, L P (1978)
The minimal water activity (alphaw) for growth was correlated with enterotoxin A formation by two strains of Staphylococcus aureus in a salt mixture broth. Within 7 days at 30 degrees C both strains grew and formed enterotoxin A minimally between alphaw 0.864 and 0.867, but at 25 degrees C, the minimal alphaw for both activities was increased to between 0.870 and 0.887 after a 2-week incubation.